Association of depression with glycaemic control in people living with diabetes in low- and middle-income countries: a systematic review and meta-analysis - Yang Zhao; Rohina Joshi; Andre Pascal Kengne; Sudha Kallakuri; Mercian Daniel; Nasheeta Peer; Jillian Hill; Kim A Nguyen; Derrick Sekgala (BMJ Global Health, 2025)
Background Depression has been found to be associated with poor diabetes control, which contributes to diabetes complications. However, the association between depression and glycaemic control remains understudied in low- and middle-income countries (LMICs) where the greatest burden of uncontrolled diabetes and diabetes complications exists. This meta-analysis examined the association of depression with glycaemic control in adults with diabetes mellitus in LMICs.Methods We performed comprehensive searches in PubMed-Medline, Scopus, Web of Science and Cumulative Index to Nursing and Allied Health Literature (CINAHL) databases to identify studies that examined the association of depression with glycaemic control. Study quality was assessed using the Newcastle-Ottawa Scale. Pooled effect estimates were expressed as ORs and mean differences (MDs) using random effects meta-analysis. Heterogeneity of effects was tested using Cochran’s Q test.Results A total of 39 studies comprising 22 456 adults with diabetes, of whom 21% had depression, were included in the meta-analysis. Depression was associated with poor glycaemic control (OR: 2.01, 95% CIs 1.41 to 2.86; I2: 90.8%; p<0.001; AOR: 1.52; 1.20 to 1.92; I2: 93%; p<0.001; MD: 0.56; 0.27 to 0.84; I2: 82%; p<0.001), with difference in effect sizes by depression diagnostic criteria (p<0.001). Age, diabetes duration, marital status and publication year had no effect on the association (all p≥0.096); while inconsistent effects on the association were observed for body mass index, male gender, sample size and region where studies were conducted. Observed publication bias (all p≤0.007 for the Egger’s test) was likely spurious.Conclusion This meta-analysis found a positive association of depression with poor glycaemic control in adults with diabetes in LMICs. The findings emphasise the importance of incorporating mental healthcare in diabetes management in low-resource settings.